Symptoms and diagnostic criteria of acquired Megacolon - a systematic literature review - Tahleesa Cuda; Ronny Gunnarsson; Alan de Costa (BMC Gastroenterology, 2018)
Abstract Background Acquired Megacolon (AMC) is a condition involving persistent dilatation and lengthening of the colon in the absence of organic disease. Diagnosis depends on subjective radiological, endoscopic or surgical findings in the context of a suggestive clinical presentation. This review sets out to investigate diagnostic criteria of AMC. Methods The literature was searched using the databases - PubMed, Medline via OvidSP, ClinicalKey, Informit and the Cochrane Library. Primary studies, published in English, with more than three patients were critically appraised based on study design, methodology and sample size. Exclusion criteria were studies with the following features: post-operative; megarectum-predominant; paediatric; organic megacolon; non-human; and failure to exclude organic causes. Results A review of 23 articles found constipation, abdominal pain, distension and gas distress were predominant symptoms. All ages and both sexes were affected, however, symptoms varied with age. Changes in anorectal manometry, histology and colonic transit are consistently reported. Studies involved varying patient numbers, demographics and data acquisition methods. Conclusions Outcome data investigating the diagnosis of AMC must be interpreted in light of the limitations of the low-level evidence studies published to date. Proposed diagnostic criteria include: (1) the exclusion of organic disease; (2) a radiological sigmoid diameter of ~ 10 cm; (3) and constipation, distension, abdominal pain and/or gas distress. A proportion of patients with AMC may be currently misdiagnosed as having functional gastrointestinal disorders. Our conclusions are inevitably tentative, but will hopefully stimulate further research on this enigmatic condition.